2020
DOI: 10.2147/jbm.s265461
|View full text |Cite
|
Sign up to set email alerts
|

<p>Blood Donor Deferral Analysis in Relation to the Screening Process: A Single-Center Study from Southern India with Emphasis on High Hemoglobin Prevalence</p>

Abstract: Donor deferral results in loss of potential, motivated blood donors, and thereby, availability of blood for needy patients. This study analyses the frequency and reasons for donor deferral, including high hemoglobin deferral, which is underreported in India. Methods: Retrospective analysis of the deferral record of whole blood donors from January 2014 to December 2018 was performed with respect to the pre-donation screening process at our center. Accordingly, the deferrals are categorized as stage1-evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 22 publications
3
20
2
Order By: Relevance
“…Studies revealed that deferral significantly increased as age increased due to abnormal blood pressure. 19,20 In the current finding, most of the donors (82.1%) were males. This was comparable with other studies conducted in Madagascar 17 and India.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Studies revealed that deferral significantly increased as age increased due to abnormal blood pressure. 19,20 In the current finding, most of the donors (82.1%) were males. This was comparable with other studies conducted in Madagascar 17 and India.…”
Section: Discussionsupporting
confidence: 50%
“…Studies showed that females were more defer than males 19,30,31 due to being more anemic compared to males. 19,20 World Health Organization and other international and national organizations advised that blood donations must be voluntary and unpaid. This ensures the availability of a constant and safe blood supply.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 20 , 21 , 22 , 23 The common deferral reasons identified in a previous study conducted at our center include the hemoglobin-based deferral followed by high blood pressure. 24 However, in the pandemic year post-lockdown phase, a minimal proportion (5.4%) of the deferral was due to the COVID-19 risk. This is probably due to the inclusion of regular blood donors, rather than first-time donors, who are well informed on the blood donation eligibility criteria and, thus, opted for self-deferral.…”
Section: Discussionmentioning
confidence: 99%